Surface magnetic flux density optimization considering effect of aligned magnetic field molding conditions of ring-shaped multi-pole anisotropic ferrite permanent magnet for DC motors - Ching-Chien Huang; Chih-Chieh Mo (Heliyon, 2024)
The ring-shaped anisotropic ferrite magnet with multiple poles boasts significant benefits for brushless DC motors (BDCMs). However, the prevalent production method involves dry magnetic field molding, making it challenging to enhance the magnetic properties. Herein, ferrite powder made from iron oxide, a by-product of the steel industry, is used as the starting material of magnets, and the differences between dry and wet molding approaches on the surface magnetic flux density of a ring-shaped multi-pole anisotropic ferrite magnet are first investigated. ANSYS MAXWELL conducted an initial simulation to achieve the design specifications of the wet molding mold. Following this, the mold was prepared for the fabrication of ring magnets. Compared to magnets prepared via dry molding, those produced through wet molding exhibit a peak surface magnetic flux density of approximately 15.9% higher, demonstrating significant potential for industrial applications and substantial enhancement of the key magnetic properties of wet molded ferrite ring magnets. To achieve increased surface flux density of ring magnets, it is common practice to utilize magnetic powders with greater magnetic properties when molding the magnets. However, this requires a costly mold redesign. In this study, higher surface magnetic flux densities can be achieved for ring magnets by simply adjusting the shape, size and magnetization direction of NdFeB permanent magnets that provide a constant aligned magnetic field in the mold without requiring any alterations to the existing mold's dimensions. The findings of this study could improve the effectiveness of existing motor designs. The usage of ring-shaped multi-pole anisotropic ferrite magnets is anticipated to witness a surge in the coming years, driven by the growth of energy-efficient motors in diverse sectors.